Solidification/stabilization of metallurgical tailings from the zinc process: environmental, microstructural, and mechanical aspects - Fernando Fante; Andrés Lotero; Hugo Carlos Scheuermann Filho; Giovani Jordi Bruschi; Maiki Mafessoli; Maria Alice Piovesan; Paulo Henrique Nogueira Metzker; Eduardo Pavan Korf; Nilo Cesar Consoli (Environmental Science and Pollution Research, 2026)
The management of metallurgical tailings from the zinc process (MTZP) involves a series of hazards due to the presence of heavy metals and sulfates in its composition. An alternative to overcome these difficulties is the use of the solidification/stabilization technique associated with the disposal in dry stacks. For this purpose, it was evaluated the environmental, microstructural, and mechanical properties of compacted metallurgical tailings from the zinc process stabilized with quicklime, Portland cement, and a mixture of both to reduce the potential contamination and increase the mechanical properties, under 7 and 28 days of curing. Analyses such as X-ray fluorescence spectrometry, X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy were conducted. Complementarily, mechanical response (unconfined strength and initial shear modulus) and batch leaching tests were executed to provide a complete understanding of treated material behavior. Stabilization with Portland cement reduced the leaching of heavy metals and was not effective in stabilizing the sulfates. The quicklime, due to the common ion effect, provided a reduction in the leaching of sulfates and some heavy metals and a better mechanical response compared to Portland cement. The use of both stabilizers produced the best combination of encapsulation of heavy metals, reduction in the leaching of sulfates, and enhancement of the mechanical properties.

Long-term performance: strength and metal encapsulation in alkali-activated iron ore tailings - William Mateus Kubiaki Levandoski; Suéllen Tonatto Ferrazzo; Maria Alice Piovesan; Giovani Jordi Bruschi; Nilo Cesar Consoli; Eduardo Pavan Korf (Environmental Science and Pollution Research, 2024)

Use of sludge from the vehicle industry and its encapsulation of toxic metals in ceramic products - Everaldo Mello de Almeida; Jonas Duarte Mota; Carolina Menegolla; Maria Alice Piovesan; Caroline Müller; André Zimmer; Eduardo Pavan Korf (Environmental Science and Pollution Research, 2023)